3-Methylcrotonylglycinuria: a new common mutation in the Portuguese population? - Fonseca, Helena (2011)
Introduction: 3-Methylcrotonylglycinuria (MCG) is an inborn error of the leucine catabolism resulting from isolated biotin-insensitive deficiency of 3-methylcrotonyl-CoA carboxylase (3-MCC), the enzyme converting 3-methylcrotonoyl-CoA to 3-methylglutaconyl-CoA. The metabolic phenotype characterizing MCC deficiency is the elevated excretion of the diagnostic compounds 3-methylcrotonylglycine and 3-hydroxyisovaleric acid, and the presence of abnormally elevated blood levels of 3-hydroxyisovalerylcarnitine (C5-OH), as determined by tandem mass spectrometry (MS/MS). Expanded newborn screening for inborn errors of metabolism using MS/MS has demonstrated that 3-MCC deficiency is one of the most commonly detected inherited organic acidurias. Patient and methods: The authors report the results of molecular studies performed in six cases in a universe of thirty patients with an increase of C5-OH in the acylcarnitine profile. Blood spot samples from newborns are collected between day 3 and 6 in Watman 903 filter paper. Acylcarnitines in samples are analysed in tandem mass spectrometer. The molecular characterization is the study of genes MCCA and MCCB that encodes the enzyme 3-MCC. Results: The six cases showed the same novel mutation p.N230D in the MCCB gene, proving that this is the most common new mutation in our population. According to the studies conducted to this new mutation using bioinformatic applications, it is considered a benign mutation, but the alignment of species and the population study conducted, showed that this mutation is responsible for the biochemical phenotype found in these cases. Discussion: Of the thirty MCC cases studied, p.N230D mutation revealed to be the most frequent new mutation. Bioinformatic analysis showed that this mutation is located in a non conserved area but the mutant residue was never present in the homologous proteins analyzed.